Serial publications - Gutiérrez Gómez, Edgar (2020)
The government on duty assesses the need for scientific productions in its most complex state sector, education. In this line, it is encouraging incentives for academic research, especially in public universities nationwide, after having cleared with a licensing process all universities in Peru. One of the indispensable prerogatives is the publication of articles in indexed journals, having published books, having developed full papers in scientific events, leading research projects among other conditions as a requirement to be immersed as research teachers.